Mistreatment of women during gynecological care in health facilities in Guinea - Diallo, Ramata; Balde, Mamadou Dioulde; Kourouma, Kabinet; Sidibe, Tiany; Sall, Alpha Oumar; Camara, Sadan; Touré, Madeleine; Diallo, Aissatou; Keita, Kaba Saran; Diallo, Abdourahmane; Barry, Fanta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Many women are victims of violence in healthcare facilities around the world. This problem remains under analysed in gynecology departments in Guinea. The aim of this study was to determine the frequency and identify the factors associated with the occurrence of client mistreatment in gynecology units. Methods: This was a descriptive cross-sectional study conducted in 15 health facilities in five prefectures of the Republic of Guinea between January 20 and February 16, 2023. Women aged 18 to 49 who agreed to participate in the interview constituted the study population. A total of 276 clients were surveyed at the discharge from gynecological consultations and care. Multivariate logistic regression was used to identify factors associated with the occurrence of mistreatment among gynecology clients, using Stata 16.0 software. Results: Acts of mistreatment were frequent in gynecology departments, including several types, essentially physical violence (28%), verbal violence (25%) and especially neglect (40.6%). Factors associated with mistreatments included the number of children, the time of occurrence and age of the client. Having 2 or more children increases the risk of abuse. At the time of occurrence, risk of exposure to physical violence, verbal abuse and all types of mistreatments during surgery/postoperative care. Being between 25 and 29 reduces the risk of exposure to mistreatment, comparing to adolescents. Conclusions: This study suggests training providers in respectful care and sensitizing them to the need to discontinue this practice in order to reduce mistreatment in gynecological care services in Guinea, while taking into account the factors highlighted by this study in order to provide clients with effective services and enable them to make better use of them.